2003
DOI: 10.3168/jds.s0022-0302(03)73954-x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicular Activity in Lactating Holstein Cows Supplemented with Monensin

Abstract: The objective of this study was to determine effects of monensin on ovarian follicular development and reproductive performance in postpartum dairy cows. Forty-eight multiparous Holstein cows were randomly assigned to receive either a control total mixed ration (n = 24) or the same diet plus 22 mg of monensin/kg (n = 24) from 21 d before anticipated calving until cows were either confirmed pregnant or were >180 d postpartum. Monensin had no effect on development of the first dominant follicle postpartum or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…However, cows supplemented with monensin conceived earlier (P B0.01), and thus had a shorter calving to conception interval (P B0.01). Those findings are in agreement with previous studies in which, dairy cows, treated with monensin, were more likely to achieve first service conception, have a decreased calving to conception interval and a decreased number of services per conception (Tallam et al 2003;Melendez et al 2007). The percentage of cows calving increased (P B0.01) by approximately 10% for cows supplemented with monensin, but was not changed (P 00.63) by grain supplementation.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…However, cows supplemented with monensin conceived earlier (P B0.01), and thus had a shorter calving to conception interval (P B0.01). Those findings are in agreement with previous studies in which, dairy cows, treated with monensin, were more likely to achieve first service conception, have a decreased calving to conception interval and a decreased number of services per conception (Tallam et al 2003;Melendez et al 2007). The percentage of cows calving increased (P B0.01) by approximately 10% for cows supplemented with monensin, but was not changed (P 00.63) by grain supplementation.…”
supporting
confidence: 83%
“…Monensin is an ionophore that affects fermentation dynamics in the rumen and shortens the postpartum interval to first ovulation in dairy cows (Tallam et al 2003). Monensin increased first service conception rates for dairy cows with a body condition score greater than 2.75 (Melendez et al 2007).…”
mentioning
confidence: 99%
“…Further evidence of improved energy balance can be seen in reproductive responses. Tallam et al (2002) concluded that cows fed a diet containing monensin ovulated for the first time postpartum five days earlier than controls, suggesting that nadir had been achieved earlier.…”
Section: The Effect Of Ionophores On the Efficiency Of Feed Use In Mementioning
confidence: 99%
“…Similar results were described by other authors (Lean et al, 1994;Hayes et al, 1996;Beckett et al, 1998). However, Tallam et al (2003) reported that the first postpartum ovulation occurred earlier in cows fed monensin than in the control group in multiparous Holstein cows and Matos et al (2004) found that monensin increased follicle size at day 54 postpartum, but did not affect ovulation rate of Nellore cows. These differences could be associated with the breed of animals and the type of feeding used in each study.…”
Section: Discussionmentioning
confidence: 97%
“…The increase in the proportion of ruminal propionic acid and the availability of glucose, could improve the partition of nutrients towards the hypothalamic-pituitary-gonadal axis, reversing the postpartum anestrus situation (Diskin et al, 2003;Hess et al, 2005). In addition, some authors reported that monensin supplementation decrease time to the first postpartum ovulation in Holstein cows, and increase follicle size at 55 days postpartum in Nellore cows (Tallam et al, 2003, Matos et al, 2004. Many studies have been carried out in order to evaluate the use of hormonal treatments to reduce the calving-conception interval (Bó et al, 2003;Baruselli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%